Assessment of the anti-nociceptive effects of fetal ventral mesencephalic tissue allografts in a rat model of hemi-Parkinson’s disease using fMRI - Chiu, Chuang-Hsin; Weng, Shao-Ju; Yeh, Skye Hsin-Hsien; Jhao, Yun-Ting; Chang, Hsien-Feng; Huang, Wen-Sheng; Cheng, Cheng-Yi; Yeh, Chun-Chang; Ma, Kuo-Hsing (Frontiers in Aging Neuroscience, 2022)
Extensive studies showed increased subjective pain sensitivity in Parkinson’s disease (PD), which appeared to be partially reversed by dopaminergic (DA) treatment. Although cell replacement represents an attractive therapeutic strategy, its potential for PD-related hyperalgesia remains unclear. We investigated re-establishment of DA function via allografting exogenic DA cells on pain hypersensitivity in a rat model of PD. We evaluated the anti-nociceptive effects of fetal ventral mesencephalic (rVM) tissue allografts in PD rats after unilateral 6-OHDA-induced toxicity in the medial forebrain bundle. The drug –induced rotation test was used to validate the severity of the nigrostriatal lesion; von Frey and thermal pain tests were employed to evaluate nociceptive function. Nociception-induced cerebral blood volume (CBV) response was measured using a 4.7-T MR system. Finally, the immunohistochemical (IHC) studies were performed and the results were compared with the imaging findings from functional magnetic resonance imaging (fMRI). The grafts significantly improved drug-induced rotation behavior and increased mechanical and thermal nociceptive thresholds in PD rats. The elevation of CBV signals significantly recovered on the grafted striatum, whereas this effect was inhibited by the D2R antagonist eticlopride in each striatum. Quantitative IHC analysis revealed the transplantation markedly increased the numbers of tyrosine hydroxylase immunoreactive cells. Therefore, we concluded transplantation of rVM tissue results in anti-nociceptive effects and improves motor function. Moreover, in vivo CBV response confirmed the key role of D2R-mediated pain modulation. Therefore, we demonstrate fMRI as a reliable imaging index in evaluating the anti-nociceptive therapeutic effects of fetal rVM transplantation in the rat model of PD.